Development Strategy, Viability, and Economic Distortions in Developing Countries - Lin, Justin Yifu; Li, Feiyue (2012)
This paper presents a three-sector static model to explore the rationale for a series of institutional distortions in developing countries. The authors argue that, after World War II, motivated by a belief in the development of state-of-the-art industries as a means for nation building, the majority of developing country governments attempted to accelerate the growth of advanced capital-intensive industries. However, since developing countries are relatively rich in labor or natural resource endowments but not in capital endowment, advanced capital-intensive industries were not adapted to the endowment structures of these developing countries at the time. Enterprises in those industries were non-viable in open, competitive markets and could not survive without government subsidization or protection. The model shows that, in order to mobilize resources into the capital-intensive, advanced sectors, it is necessary for governments to use distortionary policies such as taxes and subsidies, distortions of factor prices, directive allocation of resources, and nationalization of enterprises. Such distortions enable developing countries to set up advanced, capital-intensive industries in the early stage of their development. However, they also tend to suppress incentives, misallocate resources, and make the economy inefficient.